Cognitive function is preserved in older adults with a reported history of childhood sexual abuse - Robertson, Ian; Feeney, Joanne; Kenny, Rose (My University, 2013)
Childhood sexual abuse (CSA) is associated with mood and cognitive deficits in children and young adults. Evidence suggests that the effects of early-life adversity persist throughout adulthood; however, the impact of CSA on cognition in older adults is largely unknown. This study investigated cognitive function in older adults with a reported history of CSA. Data are from a population-based study (The Irish Longitudinal Study on Ageing) of 6,912 adults aged 50 years and older. Participants answered questions about CSA as part of a stressful life events questionnaire. Global cognition, executive function, memory (both objective and self-rated), attention, and processing speed were measured via a comprehensive battery of tests. Anxiety and depression, other childhood adversity, health behaviours, chronic disease, and medication use were also assessed. Of the total sample, 6.5% reported CSA. These individuals were more likely to have experienced other forms of childhood adversity and to exhibit poor mental health compared to those who reported no history of CSA. Multivariate regression analyses revealed, however, that CSA was associated with better global cognition, memory, executive function, and processing speed, despite poorer psychological health in this group. Future studies should aim to investigate possible reasons for this finding.
PUBLISHED
Keywords: Cognitive function; Ageing